School-Related Variables as Correlates of Quality Leaning Outcome of Senior Secondary School Students - Etan, Michael O.; Frank M., Attah; Bisong, Kenneth B.; Angioha, Pius U.; Abang, Thelma A.; Akande, Depoe (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
This study attempts to examine the extent to which school-related variables such as teacher's quality, classroom ergonometric affects the Quality Leaning Outcome of senior secondary school students. The study was a survey research design. Data was collected from 385 senior secondary school students of government-operated secondary schools in Calabar, Cross River state, using a structured questionnaire. The purposive sampling technique was used in selecting the samples from the study area. Collected data were screened and checked for errors. The data was then analysed using descriptive and parametric statistics at 0.05 significant level. Out of the 385-instrument distributed, 376 was returned and used for analysis. From the interpreted data, the result revealed that high teacher quality statistically significantly differs from low teachers' quality in terms of Quality Leaning Outcome of secondary school students. This result is because the calculated t-value of t (374) = 3.57 was higher than the critical t-value of 1.96 at p < .05. This result means that the high quality of teachers affects student academic outcome. Also, the result revealed that classroom ergonometric significantly relates to quality of academic outcome. Because the calculated r-value of 0.170* is greater than the critical r-value of 0.098 at 0.05 level of significance with 374 degrees of freedom. With these results, we can conclude that school-related variables significantly relate to quality academic outcome. Hence, there is a need for improvement in school variables in schools in the study area.